2021
DOI: 10.3390/pathogens10050621
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Backyard Pig Exposure to Highly Pathogenic Avian Influenza H5N8 Virus during 2016–2017 Epizootic in France

Abstract: In autumn/winter 2016–2017, HPAI-H5N8 viruses belonging to the A/goose/Guandong/1/1996 (Gs/Gd) lineage, clade 2.3.4.4b, were responsible for outbreaks in domestic poultry in Europe, and veterinarians were requested to reinforce surveillance of pigs bred in HPAI-H5Nx confirmed mixed herds. In this context, ten pig herds were visited in southwestern France from December 2016 to May 2017 and serological analyses for influenza A virus (IAV) infections were carried out by ELISA and hemagglutination inhibition assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…While the human-origin pandemic A(H1N1)pdm09 virus clade 1A.3.3.2 viruses were more commonly reported in backyard swine, the human H1N1 and H3N2 viruses were also detected in backyard swine in various countries suggesting reverse-zoonotic transmission events from human-to-swine. Intriguingly, the presence of avian-origin highly pathogenic viruses including H5N1 [ 12 ] and H5N8 [ 40 ] suggest the possibilities of avian-to-swine transmission. In particular, the presence of highly pathogenic avian H5N1 viruses in Nigerian backyard swine is of interest because Nigeria falls within the East Africa–West Asia flyway of the migratory birds [ 53 ] used by long-distance migratory wild birds for intercontinental migration for overwintering [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the human-origin pandemic A(H1N1)pdm09 virus clade 1A.3.3.2 viruses were more commonly reported in backyard swine, the human H1N1 and H3N2 viruses were also detected in backyard swine in various countries suggesting reverse-zoonotic transmission events from human-to-swine. Intriguingly, the presence of avian-origin highly pathogenic viruses including H5N1 [ 12 ] and H5N8 [ 40 ] suggest the possibilities of avian-to-swine transmission. In particular, the presence of highly pathogenic avian H5N1 viruses in Nigerian backyard swine is of interest because Nigeria falls within the East Africa–West Asia flyway of the migratory birds [ 53 ] used by long-distance migratory wild birds for intercontinental migration for overwintering [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…One highly pathogenic avian influenza H5N8 virus was detected in a backyard swine in France during an H5N8 outbreak among French poultry during 2016–2017. The HI assay confirmed that one backyard swine had antibodies against H5 clade 2.3.4.4b and identified that avian origin H5N8 virus would have been transmitted from domestic ducks raised on the backyard farm to the swine [ 40 ]. No clinical signs of disease were reported from the infected backyard swine.…”
Section: Africamentioning
confidence: 99%
See 3 more Smart Citations